O papel da creatina e do exercício físico nas convulsões induzidas por pentilenotetrazol em ratos - Rambo, Leonardo Magno (2013)
Epilepsy is among the most common neurological disorders around the world. Even with the advances in the pathophysiological studies and treatment of this condition, about 30% of the patients do not present satisfactory response to pharmacological treatment available today. In this sense, the searches for new therapies that can help the treatment of this condition are essential. The present thesis aimed to investigate the effect and the mechanisms involved in creatine supplementation and exercise training on a seizure model induced by PTZ. The results presented here showed that exercise training, acute and chronic creatine supplementation as well as the combination between exercise training and chronic creatine supplementation, protected against PTZ-induced seizures. Also, exercise training increased the SOD activity and the thiol groups content per se. Additionally, the chronic creatine supplementation also increased the thiol group content and the acute creatine administration increased the mitochondrial membrane potential () per se. Moreover, also the chronic supplementation and the physical activity program, as well as their combination controlled the increase in the lipoperoxidation and protein carbonylation, the decrease in thiol group content and in the activity of SOD, CAT and Na+,K+-ATPase, induced by the injection of PTZ. In the same way, the acute creatine treatment prevented against the decrease in the Na+,K+-ATPase and xanthine oxidase activity, the decrease in the ATP and ADP content, the increase in the AMP, adenosine, inosine, uric acid content, carbonylated protein and lipoperoxidation, after seizures induced by PTZ. The results indicate that the increase in antioxidant defenses and the maintenance in the energetic storages promoted by exercise training and acute and chronic creatine supplementation can be the putative mechanisms involved in protection against seizures and neurochemical changes induced by PTZ injection. Taking into account the high energetic requirement in disorders with epileptic phenotype, and the known oxidative component involved also in epileptogenesis and in spread of seizures, the exercise training and the creatine supplementation can be considered adjunct therapies in potential to treatment of conditions that present epileptic phenotype.